THE EFFECT OF EVAPOTRANSPIRATION DEFISIT 0N WATER PRODUCTIVITY AND GROWTH OF SOYBEAN PLANTS (Glycine max L. Merrill) - Wijaya, I Ketut Adi Putra (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
Soybean is an efficient source of vegetable protein. National soybean production continues to decline during2010-2012. The lowproductivity of soybean is one of them caused by drought stress. Therefore, it is necessary touse cultivation techniques which can improve the efficiency of water use, ie with deficit irrigation. Deficitirrigation can be evaluated by calculating the amount of crop water productivity. The purpose of the research isto calculate andcompare themagnitude of cropwater productivity andgrowth of three varieties of soybeanplantsin each treatment evapotranspiration deficit. Researchwas conducted in September 2014 -December 2014 in thegreenhouse of IntegratedField Laboratory and LaboratoryofWaterResourcesand LandDepartment ofAgriculture,University of Lampung.The experimentwas conducted using a factorial in completely randomized design (CRD)with two factors that is soybean varieties which consists of three varieties: Kaba, Tanggamus, and Willis anddeficit ETC which consists of three levels: 1.0 x ETC, 0.8 x ETC, and 0.6 x ETC. Data were analyzed with Analysis OfVariance (Test F), then continued by LSD test at the significance level of 5% and 1%. Results showed that: (1)based on the total leaf area, Kaba and Wilis varieties of soybean plants have started stress at week 2nd in thetreatment ET2 (0,8 x ETC), varieties Tanggamus began stress on the 3rd week of the treatment ET3 (0,6 x ETC).Eventually based on the production of soybeans plant, varieties Tanggamus andKaba remains stress in treatmentET2 (0,8 x ETC) except varietiesWillis on ET3 (0.6 x ETC), (2) the crop water productivity was not significantlydifferent between treatments except treatment Tanggamus varieties ET3 deficit (0, 6 x ETC), (3) Kaba varietieshave the highest production in the amount of 20.22 grams,while the cropwater productivity of the highest of theWilis varieties is equal to 0.5 kg/m3.Keywords: evapotranspiration, deficit irrigation, soybeans